(Role of Faraizi Movement in Revival of Muslim Identity and Peasantry Consciousness (in Nineteenth Century Bengal - KU, SZIC (The Islamic Culture "As-Saqafat-ul Islamia" الثقافة الإسلامية - Research Journal - Sheikh Zayed Islamic Centre, University of Karachi, 2019)
(Role of Faraizi Movement in Revival of Muslim Identity and Peasantry Consciousness (in Nineteenth Century Bengal